Evidence for a cyclic GMP-independent mechanism in the anti-platelet action of S-nitrosoglutathione - Gordge, M P (1998)
1. We have measured the ability of a range of NO donor compounds to stimulate cyclic GMP accumulation and inhibit collagen-induced aggregation of human washed platelets. In addition, the rate of spontaneous release of NO from each donor has been measured spectrophotometrically by the oxidation of oxyhaemoglobin to methaemoglobin. The NO donors used were five s-nitrosothiol compounds: S-nitrosoglutathione (GSNO), S-nitrosocysteine (cysNO), S-nitroso-N-acetyl-DL-penicillamine (SNAP), S-nitroso-N-acetyl-cysteine (SNAC), S-nitrosohomocysteine (homocysNO), and two non-nitrosothiol compounds: diethylamine NONOate (DEANO) and sodium nitroprusside (SNP). 2. Using 10 μM of each donor compound, mean±s.e.mean rate of NO release ranged from 0.04±0.001 nmol min(−1) (for SNP) to 3.15±0.29 nmol min(−1) (for cysNO); cyclic GMP accumulation ranged from 0.43±0.05 pmol per 10(8) platelets (for SNP) to 2.67±0.31 pmol per 10(8) platelets (for cysNO), and inhibition of platelet aggregation ranged from 40±6.4% (for SNP) to 90±3.8% (for SNAC). 3. There was a significant positive correlation between the rate of NO release and the ability of the different NO donors to stimulate intra-platelet cyclic GMP accumulation (r=0.83; P=0.02). However, no significant correlation was observed between the rate of NO release and the inhibition of platelet aggregation by the different NO donors (r=−0.17), nor was there a significant correlation between cyclic GMP accumulation and inhibition of aggregation by the different NO donor compounds (r=0.34). 4. Comparison of the dose-response curves obtained with GSNO, DEANO and 8-bromo cyclic GMP showed DEANO to be the most potent stimulator of intraplatelet cyclic GMP accumulation (P<0.001 vs both GSNO and 8-bromo cyclic GMP), but GSNO to be the most potent inhibitor of platelet aggregation (P<0.01 vs DEANO, and P<0.001 vs 8-bromo cyclic GMP). 5. The rate of NO release from GSNO, and its ability both to stimulate intra-platelet cyclic GMP accumulation and to inhibit platelet aggregation, were all significantly diminished by the copper (I) (Cu(+)) chelating agent bathocuproine disulphonic acid (BCS). In contrast, BCS had no effect on either the rate of NO release, or the anti-platelet action of the non-nitrosothiol compound DEANO. 6. Cyclic GMP accumulation in response to GSNO (10(−9)–10(−5)M) was undetectable following treatment of platelets with ODQ (100 μM), a selective inhibitor of soluble guanylate cyclase. Despite this abolition of guanylate cyclase stimulation, GSNO retained some ability to inhibit aggregation, indicating the presence of a cyclic GMP-independent component in its anti-platelet action. However, this component was abolished following treatment of platelets with a combination of both ODQ and BCS, suggesting that Cu(+) ions were required for the cyclic GMP-independent pathway to operate. 7. The cyclic GMP-independent action of GSNO, observed in ODQ-treated platelets, could not be explained by an increase in intra-platelet cyclic AMP. 8. The impermeable thiol modifying agent p-chloromercuriphenylsulphonic acid (CMPS) produced a concentration-dependent inhibition of aggregation of ODQ-treated platelets, accompanied by a progressive loss of detectable platelet surface thiol groups. Additional treatment with GSNO failed to increase the degree of aggregation inhibition, suggesting that a common pathway of thiol modification might be utilized by both GSNO and CMPS to elicit cyclic GMP-independent inhibition of platelet aggregation. 9. We conclude that NO donor compounds mediate inhibition of platelet aggregation by both cyclic GMP-dependent and -independent pathways. Cyclic GMP generation is related to the rate of spontaneous release of NO from the donor compound, but transfer of the NO signal to the cyclic GMP-independent pathway may depend upon a cellular system which involves both copper (I) (Cu(+)) ions and surface membrane thiol groups. The potent anti-platelet action of GSNO results from its ability to exploit this cyclic GMP-independent mechanism.